2011
DOI: 10.1097/scs.0b013e31820fe1af
|View full text |Cite
|
Sign up to set email alerts
|

Numb Chin Syndrome as a Manifestation of Possible Breast Cancer Metastasis Around Dental Implants

Abstract: Numb chin syndrome, sometimes called numb lip syndrome, is an uncommon but well-recognized symptom in medical oncology. It may be a metastatic neurologic manifestation of malignancy, often with no clinically visible pathologic finding. The authors report a numb chin syndrome as a manifestation possible breast cancer metastasis around dental implants in a 69-year-old woman. The patient was presented with complaint of numbness in the lower jaw. Medical anamnesis revealed a metastatic breast carcinoma (CA). Radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…In MRI examination of the head and neck, some changes were seen in the cervical spine (C2-3) as evidence of metastasis from her previous tumor. Several studies have noted the occurrence of metastasis in the spine and spinal cord in patients with malignancies associated with malignancy-related mental neuropathy [2,5,9,27]. In previous studies on patients with mental neuropathy, mandibular imaging often showed a bony lesion at the time of admission of most cases (unlike our case) [4,5,28], and also in some cases, the lesion was detected later [29].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In MRI examination of the head and neck, some changes were seen in the cervical spine (C2-3) as evidence of metastasis from her previous tumor. Several studies have noted the occurrence of metastasis in the spine and spinal cord in patients with malignancies associated with malignancy-related mental neuropathy [2,5,9,27]. In previous studies on patients with mental neuropathy, mandibular imaging often showed a bony lesion at the time of admission of most cases (unlike our case) [4,5,28], and also in some cases, the lesion was detected later [29].…”
Section: Discussionmentioning
confidence: 54%
“…For example, in case of multiple sclerosis (a demyelinating disease), it is obvious that it can cause neuropathy in various parts of the body including the maxillofacial region. [1][2][3][4][5][6][7][8][9]. While mental neuropathy can be associated with some benign conditions and diseases, it should not be considered a typical and banal symptom.…”
Section: Introductionmentioning
confidence: 99%
“…Orthokeratinized odontogenic cyst is a developmental odontogenic cyst described by Schultz in 1927 [3] as an orthokeratinized variant of the formerly called Odontogenic Keratocyst, which is today known as the Keratocystic Odontogenic Tumour (KCOT). OOC was described as distinct individual entity from other odontogenic cysts by Wright in 1981 and the term Orthokeratinized Odontogenic Cyst was given by Li et al in 1998 which is the most widely accepted term at present [4,5]. This lesion is located mainly in the molar and ramus region but its occurrence in the condyle is rare.…”
Section: Discussionmentioning
confidence: 99%
“…The numb lower lip periodically presents as a manifestation, and even presenting symptom, of malignant disease. Review of the recent literature reveals that the causative tumours are diverse: mandibular central mucoepidermoid carcinoma, leukaemia, breast cancer, colorectal cancer, osteosarcoma, as well as two lymphomas which have presented to the author during 20 years of clinical practice. Lung adenocarcinoma is the most common cell type in females (smokers and non‐smokers).…”
Section: Discussionmentioning
confidence: 99%